STRATEGI PENGUATAN RESILIENSI BISNIS MENUJU SUSTAINABILITY PADA PELAKU UMKM DI BANYUMAS - Ika Rahmawati; Anur Inayati; Restu Frida Utami (Jurnal Terapan Ekonomi dan Bisnis, 2026)
The survival of MSMEs to this day is a sign of the strength of the business management they employ and the support they receive from various parties. Banyumas Regency is one of the areas that is quite aggressive in the growth of MSMEs; currently, there are 8,557 registered MSMEs. Among them are several business owners who are members of the Aisyiyah women's empowerment movement. The purpose of this community service activity is to provide insight into the concepts of marketing strategy, digital technology, socialization of sustainable development, simple financial record-keeping, and business communication. The methods used in this activity consist of 4 stages: observation, socialization and training, monitoring and evaluation, and final report preparation. The results of the activity were obtained thru pre-tests and post-tests, where at the beginning of the socialization and training, about 30% of the participants understood the importance of business sustainability, and after participating in this activity, this increased significantly, with 70% of the participants able to understand the socialization and training materials. Therefore, it is hoped that from this activity, all participants will be able to seriously implement the training materials and practices as a strategy for resilience toward the sustainability of their businesses. Keywords: MSMEs, Marketing Strategy, Digital Technology, Business Communication, Business Resilience, Sustainability.